Evaluation of Amygdalin (B17) and Cucurbita pepo (Pumpkin seed) Activity Against Blastocystis from Diarrheic Patients in Baghdad, Iraq: in Vitro Study (Baghdad Science Journal, 2022)
Blastocystis is a ubiquitous human and animal protozoa that inhabit the gastrointestinal tract. Metronidazole is considered the standard drug for the treatment of Blastocystis infection; however, there is growing evidence of treatment failure, hazardous side effects, and appearance of strains resistant to metronidazole. In the last era, many studies have been implicated in the quest for new treatments for Blastocystis infection, especially natural products. Attention has been focused on the effect of Amygdalin (B17) and pumpkin seed on eradicating parasitic infections. The current work was built up to explore the in vitro efficacy of two natural compounds, Amygdalin (B17) and pumpkin seeds against Blastocystis isolated from symptomatic patients. In vitro incubation of the parasite with B17 (200, 400µgmL¯¹), pumpkin seed (200, 400 µgmL¯¹) and metronidazole (100, 150µgmL¯¹) was counted at different periods (one, two, twenty-four and forty-eight hours) and morphological changes were evaluated using Light Microscope. Blastocystis detected from patients with symptoms was subtype 1. The B 17 and pumpkin seed demonstrated statistically significant (p<0.05) growth reduction of Blastocystis in culture. Such results showed the possible therapeutic effects of B 17 and pumpkin seed against blastocystosis as effective safe natural alternatives.